2015
DOI: 10.1007/s00167-015-3769-3
|View full text |Cite
|
Sign up to set email alerts
|

Good long-term results following cementless TKA with a titanium plasma coating

Abstract: IV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
17
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 32 publications
5
17
0
Order By: Relevance
“…The implant system used in the present study has been used for many years in our clinic, with an overall 10-year survival rate of around 95%. Notably, this is in line with the survival rate reported in the peer-reviewed literature and in the UK National Joint Registry for the study device [ 18 , 32 ]. It has to be noted that the 10-year survival rates in the present study do not largely differ from the “Benchmark” of 95%, i.e., the upper limits of the confidence intervals were greater than or approached 95%.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The implant system used in the present study has been used for many years in our clinic, with an overall 10-year survival rate of around 95%. Notably, this is in line with the survival rate reported in the peer-reviewed literature and in the UK National Joint Registry for the study device [ 18 , 32 ]. It has to be noted that the 10-year survival rates in the present study do not largely differ from the “Benchmark” of 95%, i.e., the upper limits of the confidence intervals were greater than or approached 95%.…”
Section: Discussionsupporting
confidence: 88%
“…Our definition of focal osteolysis was any progressive osteolytic lesion at the bone–implant interface [ 17 ]. Our definition of loss of fixation was a continuous RLL greater than 1 mm in all zones, or a change in the position of the implant [ 18 ]. Mechanical axis alignment was measured via long-leg standing lower extremity radiographs both preoperatively and postoperatively.…”
Section: Methodsmentioning
confidence: 99%
“…Although cementless TKA prostheses have been first developed over three decades ago, recent advances in implant manufacturing and engineering have substantially improved their clinical success rate as demonstrated by emerging recent reports. 3,4,6,[8][9][10][11][12][13][14] In this study, we demonstrated excellent survivorship and clinical outcomes of cementless TKAs that utilized highly porous titanium-coated base plates at mean follow-up of 36 months. There are several limitations to this study.…”
Section: Discussionmentioning
confidence: 97%
“…In several recent reports, these newer generation implants have demonstrated comparable to superior results to the gold-standard cemented protheses. In addition, their clinical success has been demonstrated in patients who had altered bone quality 1,3,4,[8][9][10][11][12][13][14][15][16] such as rheumatoid arthritis (RA), elderly patients, and those with knee osteonecrosis. 3,4 One of the increasingly utilized newer generation cementless implants are the trabecular metal-based tibial base plates which are produced using additive manufacturing or three-dimensional printing technology.…”
mentioning
confidence: 99%
“…[10][11][12] Recent advances in cementless TKA designs have shown excellent results, with several studies demonstrating survivorship rates above 90% at mid-to long-term follow-up. [13][14][15][16][17] In fact, a recent metaanalysis reported that cementless TKA had a better all-cause survivorship when compared with cemented fixation. 18 While some authors recommend the use of antibioticimpregnated cement for primary TKA, 19,20 others have reported no significant benefits of its use.…”
mentioning
confidence: 99%